BODY MANAGEMENT IN MAGAZINES SUPERINTERESSANTE AND GALILEU: A NEW ENIGMA TO THE CIENTIFIC INFOTEINMENT - Damiati, Djaine [UNESP] (Univ Nac Cordoba, Centro Estudios Avanzados, 2016)
In the second half of the twentieth century a distinctive type of print publication, able to transit between scientific information and entertainment, that would culminate in what we today call scientific infotainment, gained notoriety among the mass media, first around Europe and later spreading to the world. Legitimate representatives of this genre in Brazil, the magazines Superinteressante and Galileo, were created respectively in 1987 and 1995, with language and graphic design especially targeted to the younger audience, diffuse news about the potential of science and technology until the present day, consequently serving not only a publishing market segment still not so well explored, but also a demand triggered by the integration of the country into the world market, consolidated in the early 90s. This work analyzes, through a historical study of the editorial genre, interviews with the editors in chief, and thematic analysis of the copies published between the years 2004 and 2014, how the structure of the fantastic narrative is maintained as the main strategy to produce meaning. This article attempts to demonstrate that the ancient enigmas that starred in the narratives inspired by fantastic realism, of which originated the publications, leave the stage to give space to the subject areas related to the management of the body that now emerges as a new enigma to be deciphered by science. The enigma of the contemporary fantastic narrative should be invested with enough power to boost sales of copies, and for that reason the malleability of the new body presented by the magazines converges to an adaptation to the cyber paradigm, from which emerge the sciences capable of providing the most fantastic and desired transformations.
Keywords: body management; cybernetics; narrative; technoscience; infotainment